Hormonal regulation of hippocampal dendritic morphology and synaptic plasticity - Moult, Peter R (Landes Bioscience, 2008)
The peripheral functions of hormones such as leptin, insulin and estrogens are well documented. An important and rapidly expanding field is demonstrating that as well as their peripheral actions, these hormones play an important role in modulating synaptic function and structure within the CNS. The hippocampus is a major mediator of spatial learning and memory and is also an area highly susceptible to epileptic seizure. As such, the hippocampus has been extensively studied with particular regard to synaptic plasticity, a process thought to be necessary for learning and memory. Modulators of hippocampal function are therefore of particular interest, not only as potential modulators of learning and memory processes, but also with regard to CNS driven diseases such as epilepsy. Hormones traditionally thought of as only having peripheral roles are now increasingly being shown to have an important role in modulating synaptic plasticity and dendritic morphology. Here we review recent findings demonstrating that a number of hormones are capable of modulating both these phenomena.